Hospitalization-Based Major Comorbidity of Inflammatory Bowel Disease in Canada - Charles N Bernstein; Alice Nabalamba (Canadian Journal of Gastroenterology)
OBJECTIVE: To define the patterns of hospitalization for known major comorbidities associated with inflammatory bowel disease (IBD) in Canada.